Extra corporeal shock wave lithotripsy and intracorporeal laser lithotripsy for distal ureteric calculi - a comparative study of efficacy and safety (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13231 J. Dhaka Med. Coll. 2012; 21(1): 8-11